ANALISIS PROSES BERPIKIR MAHASISWA DENGAN KECEMASAN TERHADAP MASALAH MATEMATIKA HOTS BERDASARKAN FASE KERJA MASON - Suci Wulandari Wulandari; Sri Novia Martin; Widdya Rahmalina (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2022)
This research was motivated by the anxiety of students of mathematics education study program towards HOTS mathematics problems. This anxiety affected the quality of their thought processes. Therefore, the purpose of this study was to analyze the thought processes of students with anxiety feeling about HOTS math problems based on Mason's work phases, namely entry, attack, and review. This research was a qualitative descriptive research. The datas in this study were obtained from mathematics anxiety questionnaire, HOTS mathematics test and interviews. Based on the analysis of the data collected, it could be concluded that students with high levels of anxiety fulfill the phase “entry“ only on aspect “want”, the phase “attack” was only in the aspect ”try”, but did not meet the phase “review”. Students with moderate levels of anxiety met the phase “entry” at aspect “know”, “want” and “introduce”, phase “attack” on the aspect “try” and “maybe”, but did not meet the phase “review”. Students with low anxiety levels met the phase “entry” at aspect “know”, “want” and “introduce”, the phase “attack” on the aspects “try”, “maybe” and “introduce”, but also does not meet the phase “review”.